Tunneling spectroscopy in normal/ferromagnetic d-wave superconductor silicene junctions - Zhao, Fuhai; Li, Hong; Yang, Xinjian (Physica. C, Superconductivity, 2019)
•Using BTK theory studied tunneling conductance in normal/FdS silicene junctions.•The normalized conductance strongly depend on the perpendicular electric field(EZ) and the exchange field(h) in FdS, the crystal orientation of the dS and the relative orientation of EZ and h.•When α=π/4 and 0<lEz−λSO<h, a dip appears in the conductance spectrum at eV=h while for lEz−λSO≥h case there are two dips at eV=h and eV=lEz−λSO, respectively.•When α=0, the zero-bias conductance peak splitting is obtained as increasing h for anti-parallel configuration.•The result can be used to determine the pairing symmetry of FdS. The tunneling conductance in normal/ferromagnetic d-wave superconductor (N/FdS) silicene junction is studied based on Blonder-Tinkham-Klapwijk (BTK) theory. It is demonstrated that the amplitude of the normalized conductance strongly depends on the applied electric field (EZ) and the exchange field(h) in FdS, the crystal orientation of the dS (α) and the relative orientation of EZ and h. When α=π/4, a dip appears in the conductance spectrum at eV=h for 0<lEz−λSO<h with λSO the spin obit coupling term. In the case of lEz−λSO≥h, however, double dips appear at eV=h and eV=lEz−λSO, respectively. When α=0, the zero-bias conductance peak splits into two peaks as increasing h for anti-parallel configuration. Thus, the obtained result can serve as a method to identify the pairing symmetry of FdS.